Learning Through Celebration: A Systematic Review on the Educational Potential of Festivals in Adult and Community Educatio - Rey Ahumada, Claudio (2026)
This article presents a systematic review of the use of celebrations and festivals as educational strategies in community and adult learning contexts. Following the PRISMA 2020 protocol, 40 studies published between 1988 and 2025 in Ibero-America and Europe were analyzed. The central research question was How have celebrations been employed as pedagogical strategies in community and adult education? The findings indicate that celebrations function as spaces for situated, experiential, and intergenerational learning, enhancing cultural identity, fostering social cohesion, and motivating learners with fragmented educational trajectories. At the same time, the review highlights methodological limitations and challenges to institutional sustainability. It argues for conceptualizing celebrations as “open classrooms” that bridge culture, community, and pedagogy, and it underscores the need to integrate them into educational policies that strengthen youth and adult education.